2013
DOI: 10.12659/msm.889337
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year treatment outcomes including blood cell count disturbances in patients with simple renal cysts

Abstract: BackgroundThe simple renal cyst is the most common benign kidney disease. It may cause pain and hypertension, especially if significantly enlarged. As in polycystic kidney disease, blood cell count disturbances are frequently observed in simple renal cysts. The aim of our study was to assess such disturbances, changes in blood pressure, and complication rate in our patients undergoing surgery due to simple renal cyst in the last 10 years.Material/Methods210 patients with simple renal cysts were underwent surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Approximately 2% to 4% of SRCs may become symptomatic (abdominal pain or hematuria) owing to increasing size (6-8 cm) or a complication like infection, hemorrhage, or rupture [ 6 ]. Numerous studies have reported that renal cysts can cause hypertension, which frequently resolves after cyst removal [ 9 ] or aspiration [ 10 ]. One surgical study involving treatment of patients with large renal cysts (mean cyst size, 7.45 cm) suggested a beneficial effect on blood pressure (overall decrease or antihypertensive therapy reduction) in 62% of patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 2% to 4% of SRCs may become symptomatic (abdominal pain or hematuria) owing to increasing size (6-8 cm) or a complication like infection, hemorrhage, or rupture [ 6 ]. Numerous studies have reported that renal cysts can cause hypertension, which frequently resolves after cyst removal [ 9 ] or aspiration [ 10 ]. One surgical study involving treatment of patients with large renal cysts (mean cyst size, 7.45 cm) suggested a beneficial effect on blood pressure (overall decrease or antihypertensive therapy reduction) in 62% of patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%